Interplay of EXO70 and MLO proteins modulates trichome cell wall composition and susceptibility to powdery mildew - Huebbers, Jan W; Caldarescu, George A; Kubátová, Zdeňka; Sabol, Peter; Levecque, Sophie C J; Kuhn, Hannah; Kulich, Ivan; Reinstädler, Anja; Büttgen, Kim; Manga-Robles, Alba; Mélida, Hugo; Pauly, Markus; et al. (The Plant cell, 2024)
Exocyst component of 70-kDa (EXO70) proteins are constituents of the exocyst complex implicated in vesicle tethering during exocytosis. MILDEW RESISTANCE LOCUS O (MLO) proteins are plant-specific calcium channels and some MLO isoforms enable fungal powdery mildew pathogenesis. We here detected an unexpected phenotypic overlap of Arabidopsis thaliana exo70H4 and mlo2 mlo6 mlo12 triple mutant plants regarding the biogenesis of leaf trichome secondary cell walls. Biochemical and Fourier transform infrared spectroscopic analyses corroborated deficiencies in the composition of trichome cell walls in these mutants. Transgenic lines expressing fluorophore-tagged EXO70H4 and MLO exhibited extensive colocalization of these proteins. Furthermore, mCherry-EXO70H4 mislocalized in trichomes of the mlo triple mutant and, vice versa, MLO6-GFP mislocalized in trichomes of the exo70H4 mutant. Expression of GFP-marked PMR4 callose synthase, a known cargo of EXO70H4-dependent exocytosis, revealed reduced cell wall delivery of GFP-PMR4 in trichomes of mlo triple mutant plants. In vivo protein-protein interaction assays in plant and yeast cells uncovered isoform-preferential interactions between EXO70.2 subfamily members and MLO proteins. Finally, exo70H4 and mlo6 mutants, when combined, showed synergistically enhanced resistance to powdery mildew attack. Taken together, our data point to an isoform-specific interplay of EXO70 and MLO proteins in the modulation of trichome cell wall biogenesis and powdery mildew susceptibility.
Keywords: proteiny huseníčku; rostlinné proteiny; vezikulární transportní proteiny; Plant Proteins; odolnost vůči nemocem; Protein Isoforms; Arabidopsis; Disease Resistance; nemoci rostlin; Vesicular Transport Proteins; protein - isoformy; trichomy; Arabidopsis Proteins; buněčná stěna; Trichomes; Plant Diseases; Cell Wall